Employer Branding and Employee Value Proposition in Employee Performance at the Semarang Sharia State Bank - Saputro, Alif; Putranti, Honorata Ratnawati Dwi (Global Health Science Group, 2022)
This study aims to determine the effect of employee branding and Employee Value Proposition on employee performance at the Syariah Branch of Bank Semarang Branch. The population used in this study were all employees of the Semarang Branch Syariah Savings Bank. The size of the sample size is 68 respondents, with the sampling technique used is the census method or saturated sample. The source of research data is primary data, with data collection techniques using questionnaires, while the data analysis technique used is multiple linear regression. The research results seen from the multiple linear regression equation shows that employee branding and Employee Value Proposition have a positive effect on employee performance. The results of the coefficient of determination indicate that the variable employee branding and Employee Value Proposition can explain variations in employee performance variables of 66.9%. Hypothesis test results show that employee branding has a positive and significant effect on employee performance, and Employee Value Proposition has a positive and significant effect on employee performance.